2018
DOI: 10.1101/445031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extreme resistance toPotato Virus Yin potato carrying theRystogene is mediated by a TIR-NLR immune receptor

Abstract: Summary Potato virus Y (PVY) is a major potato (Solanum tuberosum L.) pathogen that causes severe annual crop losses worth billions of dollars worldwide. PVY is transmitted by aphids, and successful control of virus transmission requires the extensive use of environmentally damaging insecticides to reduce vector populations. Rysto, from the wild relative S. stoloniferum, confers extreme resistance (ER) to PVY and related viruses and is a valuable trait that is widely employed in potato resistance breeding prog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 67 publications
0
26
0
Order By: Relevance
“…The highest identity, 42%, was detected between Y-1 and TMV2 (S9 Fig.). Recently, Grech-Baran et al [42] published the genomic sequence of a TIR-NLR immune receptor identified as Ry sto in a dihaploid clone of the cultivar “Alicja”, which has PVY resistance also from S. stoloniferum in its ancestry. Comparison of the two genomic sequences from the putative start and stop codons of the genes revealed 95% identity between TMV2 and Ry sto (S10 Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The highest identity, 42%, was detected between Y-1 and TMV2 (S9 Fig.). Recently, Grech-Baran et al [42] published the genomic sequence of a TIR-NLR immune receptor identified as Ry sto in a dihaploid clone of the cultivar “Alicja”, which has PVY resistance also from S. stoloniferum in its ancestry. Comparison of the two genomic sequences from the putative start and stop codons of the genes revealed 95% identity between TMV2 and Ry sto (S10 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two genes encoding full-length proteins were similar to TMV resistance proteins in tobacco [52] and Y-1 characterising an ER with S. andigena origin in potato [17]. One of these genes, TMV2 , showed 95% identity with the recently isolated Ry sto gene of the dihalpoid clone dH ‘Alicja’ at genomic DNA sequence level [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This process requires the search for resistance genes and their incorporation into potato genotypes. This is the case of the Rysto gene taken from Solanum stoloniferum which is grafted onto chromosome number 12 of the potato and which confers resistance to the different strains of Potato virus Y (PVY) [22].…”
Section: Cultivated Varietiesmentioning
confidence: 99%